Double contrast percutaneous transhepatic cholangiographic CT in patients with obstructive jaundice: an initial experience of 7 cases. - C L Wang; Q Shi; X J Xiang; Z Z Chen; Z D Yuan; Q H Deng; H Y Zhou; X X Ren; L Cheng; Y X J Wang (Journal of the Belgian Society of Radiology, 2012)
Purpose: To explore the technical feasibility of double contrast percutaneous transhepatic cholangiographic CT (DCPCT- CT) in patients with bile duct obstruction. Methods: Seven patients with bile duct obstructive diseases were studied, including 5 males and 3 females, ranging in age from 24 yrs to 74 yrs (average: 47.7 yrs). There were 5 cases of hilar cholangiocarcinoma, 1 case of sclerosing cholangitis, and 1 case of malignant transformation of adenoma at the distal end of the common bile duct. PTC was carried out initially, involving injection of 30ml 4.5-6.0mgI iohexol. After the bile duct system was filled, CT scan was performed, and further followed by enhanced CT with intravenous injection of 300mgI/ml contrast agent. Arterial phase, venous phase, and parenchymal phase acquisitions were obtained. Raw CT images were viewed and multiplanar reconstruction (MPR), maximum intensity projection (MIP), and volume rendering (VR) image post-processing were performed. Results: DC-PCT-CT was performed successfully and bile duct drainage was carried out. Mild lesion enhancement was demonstrated in three cases in arterial phase, while all seven cases demonstrated enhancement of various degrees in venous phase. The lesions lead to track-like, asymmetrical or irregular bile duct obstructive narrowing, and in one case intra-luminal filling defect. Reliable diagnosis was suggested in all cases. MPR, MIP and VR images were useful in demonstrating precise lesion location and for surgical planning. Conclusion: In patients with bile duct obstruction, DC-PTC-CT is a feasible technique offering both important diagnostic value and drainage application.